Pengembangan Potensi Desa Sebagai Destinasi Wisata BudayaTinjauan Terhadap Desa Pasir Eurih Kecamatan Tamansari,Kabupaten Bogor, Jawa Barat - Priyanto, Priyanto; Rizkiawan, Romario (UI Scholars Hub, 2016)
This study aims to explore the potential of the Pasir Eurih Village in Taman Sari subdistrict, Bogor regency, West Java province as a destination for cultural tourism and presents some fundamental problems related to the presence of the tourist village culture. The methodology used is qualitative research method with descriptive analysis. The results showed that the overall potential of the Pasir Eurih Village as a destination for cultural tourism are many and diverse as the existence of rural communities that still adhere to the Sundanese culture, the typical landscape of rural with a backdrop of Mount Salak, village location close to tourist destinations culture Kampung Sindang Barang, village community activities such as ornamental fish farming, cultivation, activities cottage industry of footwear (slippers and shoes), and also the existence of a historical site where the water reservoir. Some existing problems such as not optimal quality of human resources, facilities and infrastructure, promotion. This can be overcome with the active participation of various stakeholders especially the local cultural tourism village.